LOSS DAN GAIN PADA TERJEMAHAN BUKU HUKUM THE CONCEPT OF LAW KARYA H. L. A HART KE DALAM VERSI BAHASA INDONESIA “KONSEP HUKUM” - Hanifa Pascarina; M.R. Nababan; Riyadi Santosa (Prasasti: Journal of Linguistics, 2017)
This research aims to: (1) identify what is omitted (Loss) and what is added (Gain), (2) discover the causes of Loss and Gain, (3) determine the level of accuracy, (4) determine the level of acceptability, (5) determine the level of readability of translation in the legal book The Concept of Law.